OPTIMIZATION OF FATIGUE LIFE OF TRANSMISSION SHAFT BASED ON RESPONSE SURFACE METHOD - LIU LongJie; ZHAO LiHui; SHI ChengMiao; ZHENG SongLin; WENG Shuo; LIU XiangZhen; DAI Lei (Jixie qiangdu)
In view of the fatigue failure of the transmission shaft in advance, the study of the stress state and life is carried out. Through the analysis of the actual measured load, the cause of the fatigue failure of the drive shaft in advance is the inconsistent output load of the left and right splines. The finite element model of the transmission shaft is established by using finite element software, and the maximum stress at the root of the right tooth of the transmission shaft is obtained, which is the weak part of the transmission shaft. The response surface method and genetic algorithm are used to optimize the structural parameters of the transmission shaft（tooth root fillet, spline transition arc, and arc groove depth）. After optimization, the stress of the weak part of the transmission shaft tooth root is reduced by 28.3%. The fatigue life of the transmission shaft is increased by five times, and the reliability is higher. Finally, the fatigue test is carried out on the scaled down sample. The test result shows that the life of the drive shaft is doubled. The effectiveness of the optimization method is verified through experiments, and the method has certain reference significance for the optimization of shaft parts in the future.